MANFAAT HASIL BELAJAR “MEMBUAT POLA BUSANA PESTA SISTEM DRAPING” SEBAGAI KESIAPAN MENJADI PATTERN MAKER DI BUTIK - Yanti Suryani; As As Setiawati (Fesyen Perspektif, 2015)
Problems in this research study on the use of learning outcomes makes fashion pattern draping system in preparing students to become a pattern maker in the boutique. This research was conducted at SMK Negeri 2 Baleendah in class XII students. The aim of this study was to obtain data on learning outcomes make a party dress pattern draping system, in terms of competence knowledge draping , pattern making tools and materials, image understanding, image analysis models, installation Bodyline, and pattern making a party dress draping system. The method used is descriptive method. The samples used in this study is the sample totaled 32 people. Data collection techniques such as questionnaires. The findings showed that the benefits of learning outcomes make a party dress pattern draping system in terms of competence knowledge draping , pattern making tools and materials, image understanding, image analysis models, installation Bodyline, and pattern making party dress draping systems, most of the students already understand the material provision of learning that can be used as a pattern maker in readiness into the boutique